Effet de genre : le paradoxe des études d’informatique - Isabelle Collet (Tic & Société, 2011)
Among the technical and scientific studies, the evolution of the computer sciences draws attention. From the 1980s, more and more men have chosen this field but in the same time, the number of women has remained the same. To explain this masculinisation, we have considered several hypotheses. Our hypothesis is : the choice of studies and job is made through a mix between practices and symbolic representations. Before the micro computer apparence, IT jobs were perceived as “office jobs”, suitable for women in technical fields. Then, the representation of the computer scientist sticks on a man solely enthralled by his computer. This representation is very far from the reality the everyday job but does not disappear with the huge variety of computer use and purpose.